PERBEDAAN KANDUNGAN E.coli DAGING AYAM DI PASAR TRADISIONAL KEPUTRAN SELATAN DAN PASAR SWALAYAN ‘X’ KOTA SURABAYA - Athalla Permana; R. Bambang W (The Indonesian Journal of Public Health, 2019)
Hygiene and sanitation practices in chicken influenced Eschericia coli bacterial contamination in food. A Study conducted by Sasmita and Juwita mentioned that there was positively E.coli content in chicken meat in supermarket. Thus, the purpose of this study was to assess the difference of E.Coli content in chicken meat and personal hygiene of food handler. It was an observational study with cross sectional approach. The population of this study included traditional market sellers and supermarkets. The sample of this study consisted of 14 samples of chicken meat in which 7 samples came from the South Keputran traditional market and other 7 samples came from Supermarket ‘X’. Moreover, 7 traditional market sellers and 2 supermarkets were involved to be examined. Variables of the study were E.coli content in chicken meat from Traditional Market of South Keputran and Supermarket ‘X’ and personal hygiene. Samples of chicken meat was done by accidental sampling. Data were collected through interview and observation, whereas the difference of E-Coli content was analyzed using statistical test. The results of this study indicated that one of chicken meat samples positively contained E.Coli bacteria, and no significant differences of the E.coli content were found on the chicken meat samples from both the Traditional Market of South Keputran and Supermarket ‘X’. The suggestion that can be given to Supermarket ‘X’ seller is to control and pay close attention to the sanitation process from suppliers to retails